Peran Pendidikan Agama Islam dalam Pembentukan Kehidupan Sosial di Masyarakat - Subli Subli; Kamaliah Kamaliah (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2022)
As a prospective educator who will be required to grow and develop the basic potential of students and their tendencies towards something of interest in accordance with existing abilities and talents, it is important for us to know about the basic potentials possessed by humans in general because humans have a very special position. central to education. Not only as a subject but also as an object of education itself. For this reason, in this paper the author tries to explain a little discussion about the potentials of humans and the concepts in their development in terms of the philosophy of Islamic education.